2016
DOI: 10.1002/aenm.201600621
|View full text |Cite
|
Sign up to set email alerts
|

NiFe‐Based (Oxy)hydroxide Catalysts for Oxygen Evolution Reaction in Non‐Acidic Electrolytes

Abstract: NiFe‐based (oxy)hydroxides are highly active catalysts for the oxygen evolution reaction in alkaline electrolyte solutions. These catalysts can be synthesized in different ways leading to nanomaterials and thin films with distinct morphologies, stoichiometries and long‐range order. Notably, their structure evolves under oxygen evolution operating conditions with respect to the as‐synthesized state. Therefore, many researchers have dedicated their efforts on the identification of the catalytic active sites empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
731
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 831 publications
(783 citation statements)
references
References 168 publications
30
731
0
1
Order By: Relevance
“…[12] It was also demonstrated that layered hydroxides are stable and efficient OER catalysts under alkaline conditions. [16,17] Moreover, it was shown that the perovskite family with its chemical tunability of various substituting metals can exhibit excellent catalytic performance. [18] Notable in the recent research of 3d-transition-metal-based oxide catalysts is that substituting different transition metals in the material can provide a facile route to explore the full chemistry of the pristine structure.…”
Section: Introductionmentioning
confidence: 99%
“…[12] It was also demonstrated that layered hydroxides are stable and efficient OER catalysts under alkaline conditions. [16,17] Moreover, it was shown that the perovskite family with its chemical tunability of various substituting metals can exhibit excellent catalytic performance. [18] Notable in the recent research of 3d-transition-metal-based oxide catalysts is that substituting different transition metals in the material can provide a facile route to explore the full chemistry of the pristine structure.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have employed the fitted values of U from Wang and Ceder, 70 which were adapted to reproduce thermodynamic properties (ΔH of formation of the oxide), but still corrections were needed to obtain the proper thermodynamics between the different phases. 121 Similar problems arise in manganese oxides, for which site-dependent values were proposed, 54 and the most recent use of nickel oxohydroxides 122−124 with varied valences of the Ni centers and mixed Fe−Ni materials for energy-related catalysis 125,126 are foreseen. The implication of the U dependence will also affect other families of materials with applications in Li-ion batteries, water splitting, or photovoltaics such as Prussian Blue analogues, 127,128 perovskites, 129,130 or Li-ion battery cathodes.…”
Section: 106−109mentioning
confidence: 99%
“…Incorporation of a third metal ion has been proposed as a strategy to improve the activity of NiFe-LDH by affecting the conductivity and the structure of the binary catalyst [23,24,59]. Thus, we select Co 2+ as a third metal ion to synthesize ternary NiFeCo-LDH anchoring on porous BiVO4 photoanode (BiVO4/NiFeCo-LDH).…”
Section: Effect Of Ternary Nifeco-ldh On Porous Bivo4 Photoanodementioning
confidence: 99%
“…Impressively, the adjustment of metal ions in LDHs may provide more active sites and enhance the surface reaction kinetics of LDH [24]. Incorporation of a third metal ion has been proposed as a strategy to improve the activity of NiFe-LDH by affecting the conductivity and the structure of the binary catalyst [23,24,59].…”
Section: Effect Of Ternary Nifeco-ldh On Porous Bivo4 Photoanodementioning
confidence: 99%
See 1 more Smart Citation